Epidemiological Study on Acute Viral Hepatitis Outbreak in Chattogram Cantonment Area (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Acute viral hepatitis (AVH) incidence had suddenly increased at Artillery Centre and School (AC&S) at Halishahore under Chattogram (Ctg) cantonment area from 16 April 2018 to 25 June 2018. Total 1304 cases of AVH got admitted and received treatment from Combined Military Hospital (CMH), Ctg during that period.Aim: To find out the incidence, cause, predisposing factors, clinical course and to prevent such outbreaks in future.Methods: This retrospective observational study was conducted from 16 April 2018 to 25 June 2018. Total 1304 acute viral hepatitis cases were studied for epidemiological analysis to find out the causes, mode of spread, laboratory findings and outcome.Results: Among 1304 AVH cases 90% belonged to age group of 18-45 years and most of them were combatants and the age range was 5 to 60 years with mean age 30.31±11.29 years. HEV was 99% etiological factor and patients’ hospital stay were 10 to 55 days. Thirteen cases developed hepatic encephalopathy, 01 case developed acute pancreatitis and 108 cases had thrombocytopenia. No specific source of contamination was detected within AC&S, although coliform bacteria were identified in drinking water supplied to the area by WASA of Ctg city.Conclusion: We came to the conclusion that the source of infection was contaminated water supplied by WASA of Chattogram city. As we had also found that high incidence of AVH due to HEV were prevailing in Ctg city area during the same period of the outbreak.JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 3-7